Pengaruh Cross Selling, Celebrity Endorsment, Dan Kualitas Produk Terhadap Kepuasan Pelanggan Produk Clay Mask Skintific (Studi Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2021) - Yuana, Marliya Ira; Primanto, Alfian Budi; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of Cross Selling, Celebrity Endorsement, and Product Quality on customer satisfaction with Skintific Clay Mask products among 2021 students of the Faculty of Economics and Business at the Islamic University of Malang. This research employs a quantitative approach, with primary data collected through questionnaires. The sampling techniques used were purposive sampling and snowball sampling, involving a total of 95 respondents. Data analysis was conducted through several stages, including instrument testing (validity and reliability tests), classical assumption testing (normality, multicollinearity, and heteroscedasticity tests), and hypothesis testing using multiple linear regression. The results of the study indicate that the Cross Selling variable has a significant effect on customer satisfaction. In contrast, Celebrity Endorsement does not significantly affect customer satisfaction, as most respondents considered the selected celebrity figure to be less appealing. Meanwhile, Product Quality has been proven to significantly influence customer satisfaction, as the product is perceived as effective, consistent with its claims, and produces reliable results Keywords: Cross Selling, Celebrity Endorsement, Product Quality, Customer Satisfaction